Use Risk Score Method to Identify the Qualitative Risk Analysis Criteria in Tendering Phase in Construction Projects (Journal of Engineering, 2022)
The purpose of this article was to identify and assess the importance of risk factors in the tendering phase of construction projects. The construction project cannot succeed without the identification and categorization of these risk elements. In this article, a questionnaire for likelihood and impact was designed and distributed to a panel of specialists to analyze risk factors. The risk matrix was also used to research, explore, and identify the risks that influence the tendering phase of construction projects. The probability and impact values assigned to risk are used to calculate the risk's score. A risk matrix is created by combining probability and impact criteria. To determine the main risk elements for the tender phase of a construction project, this study constructed the matrix of probability and impact variables and put the periods based on the risk score. Finally, this study identified a fourth main risk group and twenty-two sub-risk factors that are appropriate for the tendering phase of construction projects in Iraq